PENGARUH KEDISIPLINAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. TRIKOMSEL OKE TBK MEDAN - Hendra Nazmi (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The object of the study is PT. Trikomsel Oke Tbk Medan, because there was a decrease in employee performance at the company. Decline in employee performance occurs due to discipline in terms of accuracy is still less than optimal and lack of attention from the company that resulted in the presence of a sense of dissatisfaction. PT. Trikomsel Oke Tbk Medan is a company engaged in the distributor of mobile phones. This research uses quantitative approach, the type of research is descriptive quantitative and the nature of this research is descriptive explanatory. Data were collected by questionnaires, interviews, and documentation studies. The method of analysis used is multiple linear regression, coefficient of determination simultaneous and partial test. The population of this research is all employees who work in PT, Trikomsel Oke Tbk Medan which amounted to 107 people. The sampling technique used a saturated sample where107 employees from PT. Trikomsel Oke Tbk Medan and 30 people from the branch office is OkeShop as a test of validity and reliability test. The results of this study indicate that the discipline and job satisfaction simultaneously and partially have a positive and significant effect on employee performance with the value of determination coefficient of 0.475 indicating that the discipline and job satisfaction affect employee performance with the percentage level 47.5% while the remaining 52.5% Is another factor that is not researched. The conclusion of this research is discipline and job satisfaction have influence both simultant and partially to employees performance at PT. Trikomsel Oke Tbk Medan.